The use of technology in sport - Emerging challenges (IntechOpen, 2018)
The development and implementation of new technology devices to help professionals, athletes, and non-athletes improve their physical fitness, performance, health, and well-being have emerged in the last few years. This book briefly overviews the current state of the art in technology applied to sports, providing examples, literature syntheses, and recent applications to sports, focused on the most important evidenced-based developments in this area. Attention is drawn to issues and unusual matters that may arise when it comes to technological innovation applied to sport. For the reader, this could be a different perspective on technological progress in physical activity. 1. Introductory Chapter: The Challenges of Technology in Sports Daniel Almeida Marinho and Henrique Pereira Neiva 2. Innovative Technology for High Performance and Mass Participation Sport Peter Smolianov, Christopher Schoen, Jaclyn Norberg, Steven Dion, Jed Smith and Kathryn Calpino